Natural Frequency Characteristic and Sensitivity Analysis of Heavy Load RV Reducer based on Dynamics Model - Ren Jun Yan Zicheng Zhang Qianghao He Wenhao (Jixie chuandong)
A 16-DOF heavy-load RV reducer dynamics model is established by the lumped parameter method. Taking the RV-550E heavy-load reducer as the research object, the natural frequency of the reducer is obtained by solving the dynamics equation, and the influence of the pin-tooth shell stiffness on the natural frequency of the system is analyzed, which provides the basis for the design of the pin-toothed shell. In order to reveal the law of the influence of system parameters on the inherent characteristics of the whole machine, the sensitivity of the natural frequency of the whole machine to the moment of inertia and stiffness of the system is further analyzed. The analysis results show that the low-order natural frequency is more sensitive to the crankshaft arm bearing stiffness, the planet carrier support bearing stiffness and the crankshaft inertia. The research results provide a theoretical basis for the structural optimization design of this type of heavy-load reducer.